Inclusão da pessoa com deficiência no trabalho: possibilidades institucionais no Serviço Público Federal. - Paula Maia Nogueira (2016)
The choice for researching about the management of disabled servers is justified by the urgent need to build an effective path that includes people with disabilities at public service, taking into account the principles of law and the social paradigm. The production available is still insufficient to face the challenges of the reality experienced by disabled servers, the human resources professionals in the institutions and by managers in general. The study aimed to know and analyze the procedures and institutional resources for inclusion of the disabled servers in a public federal university in order to contribute to the improvement of the process. This is a descriptive study of the profile of public servers with disabilities at Federal University of Minas Gerais (UFMG); using document analysis, and covering the process of stocking, admission and monitoring. The results show that the actions of inclusion of disabled servers at UFMG are guided by the legal standards without a consolidated institutional policy of Human Resources. The developed actions are isolated from each case in the logic of jobs studies and their adjustments and restrictive reports or reduction of journey that the official medical board arbitrates. The institutional mechanisms used to assess the inclusion of the server with disabilities at work are functional files, avoidance / withdrawal, sick leave, removal / relocation and assignment of bonus function. It is necessary to develop an institutional instrument that rules regular auditor server space, colleagues and their manager in order to start preventing problems arising from the non-inclusion of the server. It is also recommended the creation of a wide-ranging policy that is not restricted only to disabled servers, but incorporates the types of diversity including: race, gender, age, ethnicity, body diversity, mental suffering, sexual orientation, disability to prevent or minimize prejudice and hostility.